Rekomendacinės bibliografijos perspektyvos - Tomonis, Stasys (Knygotyra, 1973)
Recommendatory bibliography plays an important role in raising the working people’s political, ideological and cultural level, in the propaganda of political, popularscientific literature and fiction. At present methodics of compiling recommendatory editions have formed, and various types of them can be distinguished. There is an interesting experience in analysis of their effect in use.The stormy development of our life, scientific progress, the rise in cultural level of the working people has a great influence on the evolution of recommendatory bibliography in the future.The main already formed principles of recommendatory bibliography shall be retained in the nearest and furthest future. Its tasks of cultivating the Marxist-Leninist outlook of the working people, of propagating the newest achievements in science, literature and art will be retained. But essential changes are obvious too. Recommendatory bibliography at the beginning of its evolution was principally dedicated for the use of readers with a primary education. In the future the main function of recommendatory bibliography will be to recommend literature from various fields of science and the most important literature, concerning theirs specialities, to highly qualified specialists. It is obvious that in many cases recommendatory and scientific-informational bibliographies are drawing together.Changes in the structure of recommendatory editions are inevitable. They are reflected in the selection of literature. Principles of the Party spirit and scientific character of recommended literature shall be retained but in the future much more literature shall be included into recommendatory editions than it was in some of them at present. The informative moment shall be intensified in them. The qualified reader shall be able to select the most suitable literature from a wider repertory. In connection with this, types of recommendatory editions are changed. Even now some of the types are torpid, such as reading programs. The talks about book species, leaflets are gradually diminishing. Tendencies of their unification are becoming clear. The most important of them probably shall be indices of literature in greater volume. But, evidently, parallel to it miniature bibliography shall be retained which shall mostly be printed in periodicals, at the end of books, broadcasted by radio and television.There shall be changes in annotation too. Boring, short annotations proving the present interest of the book will die off. Instead of them group annotations, short introductions to the chapters of the indices with the data of facts shall be used more widely. Recommendatory indices without annotations (with short annotations of the informative character only) are perspective too.There is a tendency to shorten the data of description in recommendatory indices. In fact, shortened descriptions better emphasize the data of a book and they are fully sufficient to the reader.In the Lithuanian SSR recommendatory bibliography has developed rather widely, but lately a slackening tendency of development is noticeable. In the plans of the libraries scientific-informational bibliographies take the first place. This is natural but it is very important not to lessen attention to recommendatory bibliography. Besides the Republic library, public and other libraries must take an active part in the development of analytic and other than book forms of recommendatory bibliography, and make more active propaganda and better distribution of them through trade.In the future it is very important to study effectiveness of recommendatory editions which has recently begun in the republic, applying various methods of research and establishing close links with the sociological investigations in the reader’s interests.